(untitled) (Eureka Journal of Physical and Chemical Research, 2026)
The following procedure is applied to synthesize the hybrid polymer materials. The polymer solutions of PVA, PAAm, and PAN were independently prepared. Thus, a solution of 0.4 g PVA was dissolved in 30 mL UPW under magnetic stirring at 500 rpm during 1 h. Similarly, a solution of 0.4 g of PAAm was obtained in 30 mL of UPW. Then, the two solutions were combined and further stirred during 1 h to obtain a homogeneous mixture. After that, 0.2 g of PAN was introduced to the polymer mixture; the mixture was stirred until total dissolution. Finally, four samples from the synthesized polymer matrix were made by doping TiO₂ nanoparticles in different weight percent (0%, 2%, 4%, and 6%). The doping process was performed in the same solvent without heating. The samples were additionally treated under ultrasonication for 2 min at 80°C to achieve a uniform distribution of the TiO₂ nanoparticles. The FT-IR data indicate clear interactions between the functional groups on the surface of the nanoparticles and polymer matrix. According to XRD, the prepared material can be considered semicrystalline. TEM imaging reveals a core-shell structure of the obtained hybrid material. The optical measurements show a remarkable increase in both real and imaginary components of the dielectric constant compared to the undoped polymer matrix.